Tianfenico no tratamento das DST no Brasil - Cattapan, Altino (Brazilian Journal of Sexually Transmitted Diseases, 1995)
The author describe a lot of experiences with thianfenicol for SDT treatment and pelvic inflammatory deseases, to confirm the therapeutic efficacy in those cases. Toe thianfenicol is absorvoo for any adrninistration via and a good pacient tolerance, shaving be the value therapeutic option in the era ofbacterian resistence increase to various avalables antibiotics.